Comparison of serum cytokine levels in symptomatic and asymptomatic HIV-Leishmania coinfected individuals from a Brazilian visceral leishmaniasis endemic area. - Diego Lins Guedes; Elis Dionísio da Silva; Maria Carolina Accioly Brelaz Castro; Walter Lins Barbosa Júnior; Ana Victoria Ibarra-Meneses; Achilleas Tsoumanis; Wim Adriaensen; Johan van Griensven; Valéria Rêgo Alves Pereira; Zulma Maria de Medeiros (Public Library of Science (PLoS), 2022)
Background Visceral leishmaniasis (VL) remains an important infectious disease worldwide. VL-HIV coinfected individuals can present with atypical clinical forms of VL and have a high risk of VL relapse. Some cytokines have been described as potential markers to diagnose active VL and to predict the severity of the cases. However, few studies have included VL-HIV coinfected patients. We aimed to characterize the levels of several cytokines among VL-HIV coinfected individuals living in a VL-endemic area in Northeast Brazil. Methods This was a retrospective, cross-sectional study, aiming to estimate the levels of various cytokines in symptomatic and asymptomatic VL-HIV coinfected individuals. There were 134 study participants (35 symptomatic VL-HIV, 75 asymptomatic VL-HIV, and 24 healthy controls), all ≥ 18 years-old. Serum cytokine levels (interferon-γ, tumor necrosis factor, and interleukins 2, 4, 6, 10, and 17A) were quantified using the Becton Dickinson-BD's Cytometric Bead Array (CBA) system. Results The population mainly consisted of men (64.9%), with a median age of 35 (27-41) years. Asymptomatic individuals were younger (p = 0.013), with more years of education (p < 0.001), and were more often on antiretroviral therapy (p < 0.001) than those in the symptomatic group. Hemoglobin levels (p < 0.001), lymphocytes (p < 0.001) and CD4 count (p < 0.001) were lower in symptomatic individuals, while HIV viral loads were higher (p < 0.001). In the symptomatic VL-HIV coinfected group, we observed increased serum levels of IL-17A, IL-6, and IL-10 compared to asymptomatic patients and the healthy controls. There were no differences in the levels of all cytokines between asymptomatic VL-HIV coinfected individuals and the healthy controls. Conclusions Higher serum levels of IL-17A, IL-6, and IL-10 cytokines were observed in symptomatic coinfected individuals but not in asymptomatically infected individuals. More studies among HIV-positive persons are needed to better understand the role of serum cytokines for prognosis, to define cure and predict VL relapses in VL-HIV coinfected individuals.